2018
DOI: 10.1038/s41419-017-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

A key role for MAM in mediating mitochondrial dysfunction in Alzheimer disease

Abstract: In the last few years, increased emphasis has been devoted to understanding the contribution of mitochondria-associated endoplasmic reticulum (ER) membranes (MAM) to human pathology in general, and neurodegenerative diseases in particular. A major reason for this is the central role that this subdomain of the ER plays in metabolic regulation and in mitochondrial biology. As such, aberrant MAM function may help explain the seemingly unrelated metabolic abnormalities often seen in neurodegeneration. In the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
128
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 167 publications
4
128
0
1
Order By: Relevance
“…Therefore, MAMs are involved in steroid synthesis, phospholipid metabolism, autophagy, inflammation and mitochondrial bioenergetics. Recent studies have described the important role of MAMs in the pathogenesis of several diseases such as senescence, Alzheimer's disease, obesity and myocardial ischemia‐reperfusion . However, the role of MAMs in hypoxia‐induced mitochondrial impairment and injury in ECs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, MAMs are involved in steroid synthesis, phospholipid metabolism, autophagy, inflammation and mitochondrial bioenergetics. Recent studies have described the important role of MAMs in the pathogenesis of several diseases such as senescence, Alzheimer's disease, obesity and myocardial ischemia‐reperfusion . However, the role of MAMs in hypoxia‐induced mitochondrial impairment and injury in ECs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have described the important role of MAMs in the pathogenesis of several diseases such as senescence, Alzheimer's disease, obesity and myocardial ischemia-reperfusion. [20][21][22][23] However, the role of MAMs in hypoxia-induced mitochondrial impairment and injury in ECs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In AD pathogenesis, enhanced Ca 2+ transfer from ER to mitochondria leads to decreased ATP production, elevated ROS generation, and the activation of apoptosis (212)(213)(214). It has been reported that deficiency or inhibition of CypD can rescue the mitochondrial dysfunction and synaptic degeneration from Ab toxicity (215)(216)(217), which demonstrates mPTP's contribution to AD pathogenesis and suggests its potential role as a therapeutic target.…”
Section: Mam and Mptpmentioning
confidence: 99%
“…The prevailing theory for AD pathogenesis remains the amyloid cascade hypothesis that states Aβ accumulation, due to its increased formation or its decreased clearance (Mawuenyega et al, ), as the disease‐initiating event (see Hardy & Selkoe, ). However, there are a number of alternative or complementing theories that have been put forward over time (Area‐Gomez et al, ; Atwood & Bowen, ; Bloom, ; Friedland‐Leuner, Stockburger, Denzer, Eckert, & Muller, ; Leuner et al, ).…”
Section: Alzheimer's Disease and Mouse Modelsmentioning
confidence: 99%
“…However, there are a number of alternative or complementing theories that have been put forward over time (Area-Gomez et al, 2018;Atwood & Bowen, 2015;Bloom, 2014;Friedland-Leuner, Stockburger, Denzer, Eckert, & Muller, 2014;Leuner et al, 2007).…”
Section: Alzheimer's Disease and Mouse Modelsmentioning
confidence: 99%